2013
DOI: 10.1136/bcr-2012-007695
|View full text |Cite
|
Sign up to set email alerts
|

An instant rare complication: a fractured metallic pyloric stent

Abstract: SUMMARYMetallic pyloric stenting (also termed as metallic enteral stenting) performed endoscopically, stands as first-line treatment for malignant gastric outlet obstruction. With reported evidence, these self-expandable metallic stents (SEMS) re-enable oral food intake, preventing patients having to face invasive techniques such as surgical gastroenterostomy. We report a patient having received a covered pyloric SEMS insertion following a tumour growth causing stenosis in the gastric antropyloric region. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A case report and a study ever reported this as a late stent complication. 16 , 17 In this study, all of stent fractures occurred in the Bonastent group. However, the rates of overall stent dysfunction, restenosis, reintervention, and clinical success were still comparable between the 2 groups.…”
Section: Discussionmentioning
confidence: 54%
“…A case report and a study ever reported this as a late stent complication. 16 , 17 In this study, all of stent fractures occurred in the Bonastent group. However, the rates of overall stent dysfunction, restenosis, reintervention, and clinical success were still comparable between the 2 groups.…”
Section: Discussionmentioning
confidence: 54%
“…Complications of SEMS placement for malignant GOO, such as tumor ingrowth, tumor overgrowth, food impaction, stent migration, stent occlusion, and perforation have been reported ( 3 , 4 ); however, stent fracture is rare. In the literature, the incidence of stent fracture is reported to be 0-4.8% ( 1 , 3 , 5 - 8 ), but detailed case reports are very rare ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other minor complications, such as fever (1.4%) ( 1 ), abdominal pain (0.2-1.2%) ( 1 , 2 ), and bleeding (0.4-5.0%) ( 2 , 5 ), have also been reported. Several reports have shown stent fractures of biliary ( 6 , 7 ), esophageal ( 8 ), and duodenal stents ( 9 , 10 ). On the other hand, the details of fractures of colorectal stents have not yet been reported in the literature; the present case is the first such report and suggests a clinical approach to the long-term management of colorectal SEMSs.…”
Section: Discussionmentioning
confidence: 99%
“…SEMSs are subject to stronger shearing forces in the flexure because of peristalsis and respiratory movement, and metal fatigue due to prolonged frictional forces could be a factor in such stent fracturing. Fractures of metallic stents have previously been described with biliary ( 6 , 7 ), esophageal ( 8 ) and gastroduodenal stents ( 9 , 10 ). In the biliary and esophageal cases, thermal straining such as radiation therapy or electromechanical effort could have result in stent fracture.…”
Section: Discussionmentioning
confidence: 99%